DARI SIRIP HIU HINGGA PENYELUNDUPAN MANUSIA: KAPITALISASI DUNIA PELAYARAN NELAYAN TRADISIONAL DI WILAYAH LINTAS BATAS LAUT TIMOR - Sholihah, Fanada (Balai Pelestarian Kebudayaan Wilayah X, 2018)
Tulisan ini mengkaji tentang aktivitas nelayan tradisional Indonesia yang dinilai “menerobos batas” serta melakukan tindakan ilegal di perairan Australia. Pada 1999, terjadi perubahan target operasi, nelayan Indonesia tidak lagi melakukan penangkapan teripang, kerang lola (trochus niloticus), dan hiu untuk diambil siripnya, tetapi beralih pada “penyelundupan manusia (people smuggling)”. Kasus penyelundupan manusia telah mengonfirmasi betapa sistem kapitalis berhasil mengkooptasi aktivitas pelayaran nelayan tradisional Indonesia dengan memanfaatkan rute-rute pelayaran tradisional. Sementara, posisi mereka di wilayah perairan Indonesia semakin termarjinalkan dan terdesak oleh keberadaan nelayan asing dengan penguasaan modallebih besar dan teknologi modern. Keberadaan “pemodal besar” berhasil merubah mindset nelayan dari sekadar memenuhi kebutuhan sehari-hari (subsiten) menjadi nelayan industri yang turut aktif dalam kontestasi penangkapan ikan ilegal bahkan penyelundupan manusia.Penelitian ini hendak mengetengahkan dua permasalahan: Pertama, jalannya sistem ekonomi kapitalis dalam mengkooptasi aktivitas pelayaran nelayan tradisional di wilayah lintas batas Laut Timor.Kedua, manifestasi dari kapitalisasi aktivitas pelayaran. Akhirnya, pemerintah perlu hadir untuk melakukan penegakan terhadap aturan main dalam aktivitas pelayaran di wilayah lintas batas Laut Timor.____________________________________________________________This paper examines the activities of traditional Indonesian fishermen who are charged with violating Australia’s maritime borders and conducting illegal activities in Australian waters. In 1999, operating targets shifted as Indonesian fishermen abandoned traditional catches of sea cucumbers, lola shells (trochus niloticus), and shark fins. Instead they turned to illegal fishing and a more lucrative endeavor, people smuggling. The case of people smugglingconfirms how a turn to capitalism successfully co-opts traditional Indonesian fishing activities by utilizing traditional shipping and fishing routes for illegal activities. The position of Indonesian fisherman in Indonesia’s waters is increasingly marginalized and driven by the presence of foreign fishermen with greater capital and modern technology. The existence of “great investors” has succeeded in changing the mindset of fishermen from simply fulfilling daily needs (subsistence) and supplying local markets to becoming industrial fishermen that are also active inillegal fishing contestation and even people smuggling. This research addresses two dilemmas: First, the course of a capitalist economic system in co-opting the activities of traditional fishing voyages in the cross-border areas of the Timor Sea. Second, the embrace of capital investment in shipping and fishing in this maritime zone. Finally, as a suggested policy step, the government needs to be present to enforce the rules of the game in shipping and fishing activities in the cross-border areas of the Timor Sea.